Preliminary Investigation: StearidoStudi Pengaruh Pengadukan dan Tanpa Pengadukan Larutan Elektrolit Terhadap Struktur Kristal, Morfologi dan Rasio Magnetoresistansi Lapisan Tipis Paduan NiFe Hasil Elektrodeposisinic Acid Production by Genetically Modifie - Fahru Nurosyid; Nuryani Nuryani; Budi Purnama; Luthfiana Asry Ayuni (Jurnal ILMU DASAR, 2008)
Ni-Fe alloy thin film on Cu substrate by electro-deposition method has been made without as well as with agitation of 300 rpm for a 3 minutes deposition time and potential of 3 Volt. The characterizations consist of crystal structure test by X-Ray Diffraction method, morphology and composition test by SEM/EDX and magnetoresistance measurement with two-point probes equipment. Result of the XRD test showed that the growth of crystal structure was in the same orientation on 111, 200, 220, 311with structure of fcc. Morphology test showed that the structural images of Ni-Fe surface thin film on agitation became flat and had less grain size. The composition test results showed that composition with agitation closely Ni80Fe20 (permalloy) was 87.51% for Ni and 12.49% for Fe. The magnetoresistance measurement was less with the agitation treatment i.e. without agitation was 9.1 % and with agitation was 1.9 %.